2004
DOI: 10.4278/0890-1171-18.3.251
|View full text |Cite
|
Sign up to set email alerts
|

Association of Environmental Factors to Meeting Physical Activity Recommendations in Two South Carolina Counties

Abstract: The results support an association between level of physical activity and environmental and policy factors in two southeastern counties in South Carolina. Limitations of the study include self-reported data and cross-sectional design.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 26 publications
2
35
1
3
Order By: Relevance
“…Moreover, these results indicated that greater perceived flexibility is associated with regular participation in advocated stress management practices and healthier self-appraised lifestyle. In contrast to previous research, 4,5 we also found that greater perceived flexibility is associated with more frequent participation in physical activity. An explanation for the inconsistent findings is not readily apparent.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…Moreover, these results indicated that greater perceived flexibility is associated with regular participation in advocated stress management practices and healthier self-appraised lifestyle. In contrast to previous research, 4,5 we also found that greater perceived flexibility is associated with more frequent participation in physical activity. An explanation for the inconsistent findings is not readily apparent.…”
Section: Discussioncontrasting
confidence: 83%
“…3 Recent cross-sectional studies report little or no association between regular physical activity and workers' ability to control their work schedule. 4,5 Other studies report inconsistent associations between indicators of workplace flexibility and health behavior. For example, although some evidence suggests that workplace flexibility is associated with higher quality sleep among workers, 6,7 other research suggests that workplace flexibility may undermine sleep quality.…”
mentioning
confidence: 98%
“…Today, social ecological models form the basis, either explicitly or implicitly, for most research that addresses environmental influences on physical activity (cf. Ewing et al, 2003;Fein et al, 2004;Giles-Corti & Donovan, 2002b;Humpel et al, 2004;Sharpe et al, 2004;Titze, Stronegger, & Owen, 2005).…”
Section: Theoretical Frameworkmentioning
confidence: 98%
“…Many positive associations have been reported for each of these broad categories (eg, recreational availability [2][3][4][5][6], land use [7][8][9][10][11][12], neighborhood form [6,8,10,13], and community environment [10,11,[13][14][15][16][17][18][19]), but many null results also have been found [8,11,13,17,[19][20][21]. Several recent reviews have concluded that most studies examining the built environment and physical activity have had null associations [22,23].…”
Section: Introductionmentioning
confidence: 95%